2021
DOI: 10.1002/mar.21555
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of recipient identification and discount structure on social coupon sharing: The role of altruism and market mavenism

Abstract: This study investigates consumers' sharing of social coupons, a novel and understudied marketing strategy in which a consumer receives a coupon set where one coupon is meant to be kept and redeemed, while the other is meant to be shared with a secondary recipient. Linking the literature on marketing promotions, social influence, sharing motivations, and consumer characteristics, we examine how identification of a specific secondary recipient (e.g., family member vs. co-worker) and coupon discount structure (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…According to Zhang & Lee [43], studies comparing market mavenism and opinion leadership have only been undertaken in western markets, such as those of Germany and the United States. In addition, some researchers [9,108,109] have claimed that the datasets collected may contain distinctive cultural and normative specifications that may affect the outcomes. In the future, researchers may replicate the studies and evaluate the findings across a variety of situations, which would be beneficial.…”
Section: -Discussion and Future Research Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Zhang & Lee [43], studies comparing market mavenism and opinion leadership have only been undertaken in western markets, such as those of Germany and the United States. In addition, some researchers [9,108,109] have claimed that the datasets collected may contain distinctive cultural and normative specifications that may affect the outcomes. In the future, researchers may replicate the studies and evaluate the findings across a variety of situations, which would be beneficial.…”
Section: -Discussion and Future Research Directionsmentioning
confidence: 99%
“…Furthermore, market maven's influence diffusion processes [107]. Moreover, individuals' mavenism traits are a strong predictor of market recommendations; individuals with higher levels of mavenism are more inclined to go out of their way to recommend a product to others, even if there is no immediate personal gain [9,108,109]. According to previous research, higher degrees of mavenism traits are associated with more frequent product recommendations [110].…”
Section: Figure 5 the Antecedents And Consequences Of Market Mavensmentioning
confidence: 96%
See 2 more Smart Citations
“…Our research thus provides a preceding perspective to examine the effectiveness of shareable digital coupons and suggests that the positive effect of shareable coupons may occur at a very early stage before the actual coupon sharing per se. Hanson et al (2021) focused on the motivation of sharing shareable coupons and how shareable coupon structure affects sharing intention. They found that consumers are more likely to share coupons when socially close to the identified recipient and when the discount structure benefits the secondary recipient due to enhanced feelings of altruism.…”
Section: Shareable Coupon Literaturementioning
confidence: 99%